Perceptual discrimination difficulty and familiarity in the Uncanny Valley: more like a “Happy Valley” - Cheetham, Marcus; Suter, Pascal; Jancke, Lutz (Frontiers in Psychology, 2014)
The Uncanny Valley Hypothesis (UVH) predicts that enhanced difficulty perceptually discriminating between categorically ambiguous human and humanlike characters (e.g., highly realistic robot) evokes negatively valenced (i.e., uncanny) experience. An ABX perceptual discrimination task and signal detection analysis was used to examine perceptual discrimination (PD) difficulty along the UVH' dimension of human likeness (DHL) represented using avatar-to-human morph continua. Rejecting the implicit assumption underlying the UVH' prediction, Experiment 1 confirmed that PD difficulty was lowest for categorically ambiguous (and avatar) faces and, notably, greatest for human faces. Rejecting the UVH’ predicted positive relationship between greater PD difficulty and negative affective experience (i.e. assessed in terms of the UVH' familiarity dimension), Experiment 2 demonstrated that greater PD difficulty correlates with more positively rather than negatively valenced affective experience. Critically, this effect was strongest for ambiguous faces, suggesting a relationship between PD difficulty and familiarity more consistent with the metaphor happy valley. These findings are also consistent with a fluency amplification instead of the hitherto proposed hedonic fluency account of experienced affect along the DHL. Experiment 3 found no evidence to suggest that the reported asymmetry in the profile of PD along the DHL is attributable to a differential processing strategy (as in the other-race effect), i.e., processing avatars at a category and human faces at an individual level. In conclusion, these findings for static faces strongly challenge the UVH’ prediction, demonstrating no support for the UVH' assumed distribution of PD difficulty along the DHL and the predicted relationship between this and familiarity.